Konstrukcija spolov v Disneyevi risanki Mulan - Kolar Sluga, Breda (Monitor ISH, 2007)
The text addresses gender construction in the cartoon Mulan, produced in the 1990's by one of the leading family entertainment studios, Disney. The cartoon is unique in its choice of a female hero who makes her own decisions on her life, changing the established image and behavioural patterns of her community in the process. An in-depth analysis, however, shows that she is a single exception in an entirely patriarchal society, and that her - and consequently Disney's - achievement belongs to girlhood rather than to the world of a grown woman. The cartoon thus introduces merely a semblance of novelties (which are nevertheless very important to girls), while still lacking in new possibilities for an adult heroine.
Keywords: risani film; Mulan; filmski liki; woman; ženske; družbena vloga; stereotipi; spolna diferenciacija